Review Desain Struktur Atas Jembatan Berdasarkan Kapasitas Struktur terhadap Beban Rencana pada Proyek Revitalisasi Saluran Sungai Asam, Kota Jambi - M.Agustian Harpani; M. Nuklirullah; Diah Khairinnisa (Jurnal Kendali Teknik dan Sains, 2026)
The increasing demand for infrastructure necessitates the construction of reliable bridges with long service lives to ensure smooth mobility. This research focuses on the Griya Lingga Permai Bridge over the Asam River in Jambi City, which is scheduled for widening as part of the Asam River Revitalization program aimed at flood mitigation. Although the project faces delays due to land acquisition constraints, this postponement is leveraged as a strategic opportunity to conduct a design review of the planned bridge superstructure.The bridge is designed using a reinforced concrete "T" beam girder structure. This study aims to perform a design review of the planned superstructure. This review includes the verification of calculations, structural dimensions, and a comparison of reinforcement calculation results, which are crucial for ensuring the future safety and reliability of the bridge against design loads. To support the validation and analysis process, the research utilizes STAAD.Pro software to obtain more accurate and detailed data regarding structural capacity. The results of this study will provide solid technical recommendations for the continuation of the construction project.